A Study of International Financing Sources: Role, Importance, and Indicators in the Malaysian Economy (2005–2022) - Muhammad, Maitham N.; Sahho, Nazhan M.; Harjan, Sinan A. (PROSPECTIVE RESEARCHES, 2026)
This International finance and its sources are among the most important means of addressing the gaps between needs and available resources. Therefore, most countries worldwide, including Malaysia, are interested in this activity. This research examines the most important sources of finance in Malaysia, given the fundamental role the financial sector plays in supporting economic activity and promoting growth through a range of financial instruments and institutions that play complementary roles. This research comprises three sections: a brief conceptual overview, an analysis of the theoretical framework of finance variables and their forward and backward correlations, and an analytical framework of finance, its sources, and variables in the Malaysian economy. We present some relevant indicators and conclude with several findings and recommendations. The most important finding is that finance plays a pivotal role in promoting economic activity by efficiently directing financial resources towards various economic sectors, supporting growth, and stimulating productive investment. This ultimately addresses the research problem and confirms its hypotheses.